PENGARUH WORD OF MOUTH DAN BRAND IMAGE TERHADAP MINAT BELI KOSMETIK WARDAH DI KOTA MAKASSAR - Susianah Mokhtar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The purpose of this research is to know the simultaneous and partial influence between word of mouth and brand image to purchase intention. As quantitative research, a survey method using a questionnaire was used. The sampling technique was purposive sampling and accidental sampling. The population in this research someone that were buying in Citra Store Makassar. The sample was 95 respondents. Methods of data analysis using is descriptive analysis and multiple regression techniques. The results showed that word of mouth and brand image influenced positive and significant on purchase intention.